Synthesis and Early ADME Evaluation of a Novel Scaffold, Tetrahydro-6H-pyrido[3,2-b]azepin-6-one - Muylaert, Koen; Jatczak, Martyna; Wuyts, Benjamin; De Coen, Laurens M.; Van Hecke, Kristof; Loones, Hans; Keemink, Janneke; García, Daniel; Mangelinckx, Sven; Annaert, Pieter; Stevens, Christian V. (Synlett, 2014)
The synthesis and preliminary ADME evaluation of novel 4-(trifluoromethyl)-5,7,8,9-tetrahydro-6H-pyrido[3,2-b]azepin-6-ones is presented. The key step is a ring expansion of 4-(trifluoromethyl)-7,8-dihydroquinolin-5(6H)-ones via a Beckmann rearrangement. The rearrangement opens up possibilities to access novel unexplored scaffolds for medicinal chemistry. The biopharmaceutical profiling revealed a strong structural dependency of the druglike properties.
Keywords: bioorganic chemistry; fluorine; fused-ring systems; pyridines; ring expansion